2018
DOI: 10.1029/2018gl079536
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Correlation Between Seasonal Variations in Seismicity and Horizontal Dilatational Strain in California

Abstract: We extract significant spatially coherent strain variations from horizontal seasonal Global Positioning System (GPS) displacements in the American Southwest. The dilatational strain is largest in northern California with maximum margin-normal contraction and extension in spring and fall, respectively, consistent with the Earth's surface going down and up at those times. The northern California signal has a phase shift with respect to that in southern California and the Great Basin. For northern and southern Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…The San Andreas fault south of ~35.5° latitude is ~4–5 months out of phase with the rest of the fault, which might be due in part to its proximity to the irrigation‐controlled groundwater recharge cycle in the southern part of the Valley that is ~3 months out of phase with the rest of the Valley. Kreemer and Zaliapin () found a similar ~4‐month phase lag for peak Coulomb stress change between the northern and southern San Andreas fault, although that study was based on seasonal horizontal strain.…”
Section: Resultsmentioning
confidence: 90%
“…The San Andreas fault south of ~35.5° latitude is ~4–5 months out of phase with the rest of the fault, which might be due in part to its proximity to the irrigation‐controlled groundwater recharge cycle in the southern part of the Valley that is ~3 months out of phase with the rest of the Valley. Kreemer and Zaliapin () found a similar ~4‐month phase lag for peak Coulomb stress change between the northern and southern San Andreas fault, although that study was based on seasonal horizontal strain.…”
Section: Resultsmentioning
confidence: 90%
“…Recent studies have identified a connection between loading‐induced strain and earthquake rates in Nevada and California (e.g., Johnson et al, ; Kreemer & Zaliapin, ). Here we investigate seismicity rates in our study area to determine if they are sensitive to the horizontal strain rate changes associated with the drought periods.…”
Section: Discussionmentioning
confidence: 99%
“…MAGNET data constrain rates of motion nearly as well as continuous stations but in some cases do not well constrain seasonal oscillations since they are only occupied part of each year. Continuous stations are more common on the Sierra Nevada and LVC (since they monitor the active volcanic system), while MAGNET dominates to the east in the Great Basin where time‐variable motion was thought to be less prevalent owing to generally drier conditions in the rain shadow of the Sierra Nevada (Amos et al, ; Kreemer & Zaliapin, ; Figure ) .…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The SNR receives large amounts of precipitation concentrated in winter/spring, but with noticeable multiyear variability, alternating between periods of surplus precipitation and drought (Margulis et al, ). Several studies have highlighted the signature of these precipitation trends in deformation data, showing that observed subsidence/uplift trends at both seasonal and multiyear scales are driven mainly by surface loading/unloading from increasing/decreasing surface water and groundwater (Amos et al, ; Argus et al, ; Borsa et al, ; Kreemer & Zaliapin, ). These studies mostly focused on the vertical component of the deformation, since horizontal displacements induced by surface loading are typically much smaller (Wahr et al, ).…”
Section: Introductionmentioning
confidence: 99%